Are dietary vitamin D, omega-3 fatty acids and folate associated with treatment results in patients with early rheumatoid arthritis? Data from a Swedish population-based prospective study. Issue 6 (10th June 2017) - Lourdudoss, Cecilia; Wolk, Alicja; Nise, Lena; Alfredsson, Lars; Vollenhoven, Ronald van
Abstract : Background: Dietary intake of vitamin D and omega-3 fatty acids (FA) may be associated with superior response to antirheumatic treatments. In addition, dietary folate intake may be associated with worse response to methotrexate (MTX). The aim of this study was to investigate the association between dietary vitamin D, omega-3 FA, folate and treatment results of disease-modifying antirheumatic drugs (DMARDs) in patients with rheumatoid arthritis (RA). Methods: This prospective study was based on data from the Epidemiological Investigation of Rheumatoid Arthritis (EIRA) study, and included 727 patients with early RA from 10 hospitals in Sweden. Data on dietary vitamin D, omega-3 FA and folate intake based on food frequency questionnaires were linked with data on European League Against Rheumatism (EULAR) response after 3 months of DMARD treatment. Associations between vitamin D, omega-3 FA, folate and EULAR response were analysed with logistic regression adjusted for potential confounders. Results: The majority of patients (89.9%) were initially treated with MTX monotherapy and more than half (56.9%) with glucocorticoids. Vitamin D and omega-3 FA were associated with good EULAR response (OR 1.80 (95% CI 1.14 to 2.83) and OR 1.60 (95% CI 1.02 to 2.53), respectively). Folate was not significantly associated with EULAR response (OR 1.20 (95% CI 0.75 to 1.91)). Similar results were seen in a subgroup of patients who were initially treated with MTX monotherapy at baseline. Conclusions: Higher intake of dietary vitamin D and omega-3 FA during the year preceding DMARD initiation may be associated with better treatment results in patients with early RA. Dietary folate intake was not associated with worse or better response to treatment, especially to MTX. Our results suggest that some nutrients may be associated with enhanced treatment results of DMARDs.